A 26-year old young male with severe anemia. (2022) - Salick, Muhammad; Chaudhary, Raghav; Robledo, Fabiana Maria; Datar, Praveen B.; Htoo, Arkar; Shkolnik, Boris; Chong, Woon Hean; Chopra, Amit; Saha, Biplab K.
Abstract: Testicular choriocarcinoma is a subset of Non-Seminomatous Germ Cell Tumors (NSGT) which is considered the rarest and most aggressive testicular cancer. It primarily affects males between the ages of 25–30 years. Unlike other testicular neoplasms that carry a cure rate of 95%, choriocarcinoma has significantly lower rate of cure. Therefore, early detection and prompt treatment is necessary to improve survival. We present an unusual case of Choriocarcinoma presenting as severe anemia along with distant metastases to lung and brain. We also discuss diagnostic approach and treatment challenges in patients with Choriocarcinoma.